ANALISIS PEMULIHAN BIAYA (COST RECOVERY) DENGAN PENDEKATAN ACTIVITY BASED COSTING SYSTEM DI INSTALASI GIZI RSUD A.WAHAB SJAHRANIE - ROTUA JUNIATI SITORUS; Prof. Dr. Hj. Rusdiah Iskandar, M.Si, Ak; Dr. Musdalifah Azis, M.Si (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2019)
ANALISIS PEMULIHAN BIAYA (COST RECOVERY) DENGAN PENDEKATAN ACTIVITY BASED COSTING SYSTEM DI INSTALASI GIZI RSUD A.WAHAB SJAHRANIE Rotua Juniati SitorusProgram Magister Manajemen Dosen Pembimbing :Prof.Dr.Hj.Rusdiah Iskandar, M.Si., Ak., CADr. Musdalifah Azis, M.SiABSTRACTThe purpose of this study was to analyze cost recovery rate of nutrition installation at RSUD Abdul Wahab Sjahranie Samarinda from 2013 – 2014, based on activity based costing system. In doing the research, the data was obtained in primary data and secondary data from nutrition installation, finance department and other departments at RSUD Abdul Wahab Sjahranie Samarinda.Based on the result of the study, for the year of 2013, actual meal unit cost of first class is Rp.. 246.424 actual meal unit cost of second class is Rp. 175.311 and actual meal unit cost of third class is Rp. 151.624. In other side, the cost recovery rate of first class is only 18.00%, the second class : 20.21%,  and the third class is only 20.34%. Meanwhile, for the year of 2014, actual meal unit cost of first class is Rp.. 246.377 actual meal unit cost of second class is Rp. 185.463 and actual meal unit cost of third class is Rp. 162.846. In other side, the cost recovery rate of first class is only 18.01%, the second class : 19.10%,  and the third class is only 18.94%